COMMUNICATION DIMENSIONS WITHIN SPIRITUALITY COMMUNICATION: THE QU’RAN PERSPECTIVES - Subhan Afifi; Basuki Agus Suparno (The Indonesian Journal of Communication Studies, 2015)
The study aims to investigate the communication concepts introduced by the Qur’an. As the holy book of Moslem, the Qur’an explain  many concepts of human daily life, including communication.  Communication as sending and communication as reading in the modern communication theory can be elaborated in Qur’an perspective. This study identifies communication-related verses and analyzes the models of communication. The models are elaborated by examples from the Qur’an and the Hadith. Using interpretive paradigm, this research  uses the Qur’an as the analysis unit to explore the patterns, models, and issues of communication. The result of this research  contribute to develop eastern  perspective theory of communication.